Factors Affecting Investment Decision in Nepal - Dhungel, Basu Dev; Lamichhane, Kul Prasad (Tribhuvan University Journal, 2021)
This article, Factors Affecting Investment Decision in Nepal, has focused on the macroeconomics factors (gross domestic product, interest rate, and government expenditure) affecting the investment decision during 1975/762017/18. Based on time-series dataata macro level, this study employed Engel Grangerco integration test, as well as error correction model, investigated the short-and long-run causal relationship between gross investment and the factors influencing the investment decision of the investors, and found a statistically significant relationship between gross investment and macroeconomic variables. Furthermore, the coefficient of error correction term (-0.90) implied around a 90percent conversion to the equilibrium, showing a steady, long-run relationship between regress and regressors.